The role of innovation management and enhancing the competitive advantage of industrial enterprises - rasha mostafa mohamed eldib; sayed abdo; rehab Mahmoud elhebary (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2023)
Summary:The research was entitled the role of innovation management and the promotion of competitive advantage in industrial enterprises The problem of research is the lack of innovation management by industrial enterprises. The importance of research was to clarify and demonstrate the importance of innovation management in industrial enterprises and their effective role in supporting competitive advantage. The research relied on three axes the first is competitive advantage. The second is innovation management and the third is the role of innovation management in achieving the competitive advantage of enterprises All countries are striving to achieve economic growth based on knowledge and innovation, promote a culture of innovation between all institutions and companies, link scientific and applied research to the industry, and multiply the efforts of countries in supporting innovation to keep abreast of all these developments. All these factors have led to the need for an innovation department to be able to meet the determinations and achieve the competitive advantage of the enterprise that has innovation management and to reach the best innovative products and services It also contributes to increasing the profits of the enterprise, exploiting internal ,external opportunities innovating in methods and methods of production, thereby reducing production costs Innovation management must be treated as a comprehensive system whereby the enterprise is fully crowded to take advantage of all available opportunities and resources of all kinds, whether internal or external so that there are many industrial enterprises and companies that have adopted innovation policy to achieve competitive advantage